Faktor Risiko Kejadian Preeklampsia-Eklampsia - Bakri, Sri Intan Akmal; Fujiko, Masita; Harahap, Muhammad Wirawan (Innovative: Journal Of Social Science Research, 2024)
Hypertension in pregnancy is a broad term that includes groups of chronic hypertension, gestational hypertension, preeclampsia and eclampsia. Preeclampsia can be found in pregnancies >20 weeks with increased blood pressure and proteinuria. Eclampsia is preeclampsia with seizures (generalized tonic-clonic or focal) without other causes. The method applied is Literature Review with Narrative Review design including an in-depth study exploring the influence of maternal age, parity, history of hypertension, and obesity on the incidence of preeclampsia-eclampsia. The results of the analysis showed that age factors, both young and old, parity, together with a history of hypertension, and obesity significantly increase the risk of preeclampsia-eclampsia.